Inflammatory reaction induced by Floridosentis mugilis (Acanthocephala, Neoechinorhynchidae) in the intestine of Mugil liza - Plaul, Silvia Elena (2021)
Lebranche mullet, Mugil liza, is an important economic resource and has been recommended for aquaculture in South America. Also, this is the only mullet that breeds in Argentina. In the course of our routine investigations on the parasitic fauna of fishes from brackish waters of Samborombón Bay, Buenos Aires province, an infection of acanthocephalan worms, identified as Floridosentis mugilis was observed in juvenile lebranche mullets. These parasites were attached deeply into the intestinal wall but without piercing it. In this study we analysed the intestinal damage that F. mugilis inflicts on their hosts through the evaluation of histological sections. In the pathological analysis we observed that these parasites cause a non-specific cellular response that leads to the degranulation of eosinophilic granular cells and, consequently, the formation of a fibrous core with oedema, vascular congestion, and lymphocytic infiltration.